2012
DOI: 10.1210/en.2012-1417
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Proliferation, and Differentiation of Adult Leydig Stem Cells

Abstract: Leydig cells, the testosterone-producing cells of the adult testis, rarely turn over. However, their elimination with ethane dimethanesulfonate (EDS) is followed by the appearance of new, fully functional adult Leydig cells. The cells that give rise to the new Leydig cells have not been well characterized, and little is known about the mechanism by which they are regulated. We isolated cells expressing platelet-derived growth factor receptor-α, but not 3β-hydroxysteroid dehydrogenase (3β-HSD(neg)) from the tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
119
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(123 citation statements)
references
References 25 publications
3
119
0
1
Order By: Relevance
“…This conclusion is supported by our lineage tracing experiment. In keeping with earlier studies (27,29,57), we noted that adult Leydig cells commonly derive from (COUP-TFII + ) cells that border the seminiferous tubules, although in contrast to other studies (29), we did not find any cells coexpressing the peritubular myoid (PTM) cell marker SMA, COUP-TFII, and early Leydig cell markers. However, our findings do not exclude the possibility that, after EDS treatment, regenerating adult Leydig cells could also derive from interstitial cells that have dedifferentiated (e.g., pericytes that have switched off CD146 or PTM cells that have switched off SMA) and then either switched on COUP-TFII (pericytes) or maintained their COUP-TFII expression (PTM cells).…”
Section: Discussionsupporting
confidence: 89%
“…This conclusion is supported by our lineage tracing experiment. In keeping with earlier studies (27,29,57), we noted that adult Leydig cells commonly derive from (COUP-TFII + ) cells that border the seminiferous tubules, although in contrast to other studies (29), we did not find any cells coexpressing the peritubular myoid (PTM) cell marker SMA, COUP-TFII, and early Leydig cell markers. However, our findings do not exclude the possibility that, after EDS treatment, regenerating adult Leydig cells could also derive from interstitial cells that have dedifferentiated (e.g., pericytes that have switched off CD146 or PTM cells that have switched off SMA) and then either switched on COUP-TFII (pericytes) or maintained their COUP-TFII expression (PTM cells).…”
Section: Discussionsupporting
confidence: 89%
“…Cells on the tubule surfaces first underwent division, and then differentiated and produced T (17). These results suggested that in addition to reported perivascular locations in the interstitial compartment (18), stem cells also were located on the surfaces of the seminiferous tubules (16,19,20).…”
mentioning
confidence: 71%
“…We showed previously that functional Leydig cells can be generated by culturing Leydig cell-free seminiferous tubules with LH (16,17). With the intent to identify the tubule-associated cells that give rise to T-producing Leydig cells, seminiferous tubule fragments of comparable lengths were cultured in medium containing LH for up to 4 wk.…”
Section: Differentiation Of Stem Leydig Cells Associated With Seminifmentioning
confidence: 99%
See 1 more Smart Citation
“…The identity of the adult Leydig cell precursor population has been contentious for a number of years with pericytes, peritubular cells, fibroblasts, and endothelial cells all suggested (Jackson et al ., 1986; Kerr et al ., 1987; Teerds et al ., 1990; Davidoff et al ., 2004; O'Shaughnessy et al ., 2008b; Stanley et al ., 2012). Recent data indicates, however, that the major source of adult Leydig cells after EDS treatment are peritubular cells (O'Shaughnessy et al ., 2008b; Stanley et al ., 2012) although a contribution from other sources cannot be ruled out. The role of gonadotrophins in Leydig cell regeneration was established in early EDS studies using hypophysectomised rats or testosterone implants.…”
Section: Leydig Cellsmentioning
confidence: 99%